User Experience Analysis of LinkedIn Social Media Using Usability Metric for User Experience (UMUX) - Kamil, Muhammad Asyraf Faiz (JIEET (Journal of Information Engineering and Educational Technology), 2023)
This article presents a user experience analysis of LinkedIn using the Usability Metric for User Experience (UMUX). The study aims to assess the usability and user satisfaction of LinkedIn, identify areas for improve-ment, and propose hypotheses for future research. The problem addressed in this research is the need to evalu-ate the user experience of LinkedIn, a popular professional networking platform. The solution offered is to uti-lize the UMUX metric as a comprehensive tool for assessing usability and user satisfaction. The objectives of the study are to measure the effectiveness, efficiency, satisfaction, and overall usability of LinkedIn, as well as to identify specific areas for improvement. Data were collected through online questionnaires from LinkedIn users. The UMUX scores were calculated, indicating a moderate level of user satisfaction and perceived usa-bility of LinkedIn. These findings suggest that LinkedIn is perceived as a useful platform for professional goals, but there is room for improvement in terms of efficiency and overall user satisfaction. Hypotheses for future research include enhancing efficiency to improve satisfaction, improving overall satisfaction for in-creased engagement and retention, and optimizing the mobile experience. The study provides valuable insights for LinkedIn to enhance user satisfaction, engagement, and usability. Further research can explore additional usability metrics and investigate the impact of implemented improvements.